(untitled) (Rocklin, Calif., 2000)
Flash 5 is a development tool Web site designers use to build interactive, multimedia Web sites. Flash 5 Fast & Easy Web Development demonstrates the many uses for Flash technologies and provides everyday applications. It goes beyond the normal Flash tutorials, taking you through various Flash basics and then using applets on the accompanying CD to show you how they were created. Flash 5 Fast & Easy Web Development contains something for anyone wanting to create dynamic animations and graphics for the Web. Professional designers and beginners alike will profit from the straight-forward information provided in this visual guide to Flash technology.
Keywords: Computer graphics,Đồ họa máy tính